Composition and Utilization of Ethnomedicinal Plants in Kenyah Ethnic, Borneo, Malaysia - Waseem, Razzaq Khan; Munir, Ozturk; Fauziah, Abu Bakar; Faridah Hanum, Ibrahim; Mohamad Maulana, Magiman; Elena Gregoria Chai, Chin Fern; Abdullahi Bala, Alhassan; Volkann, Altay (East African Scholars Publisher, Kenya, 2023)
Ethnomedicinal plants are an important source of traditional medicine for many indigenous communities around the world. In Malaysia, several indigenous groups rely on these plants to treat a variety of ailments. The Kenyah people are one such group, and they have a rich tradition of using medicinal plants to maintain their health and well-being. In this study, we aimed to understand the composition and utilization of ethnomedicinal plants among the Kenyah people in Malaysia. We conducted a survey of Kenyah community members using a questionnaire and collected data on the plant species they use, the parts of the plants that are used, the methods of preparation and administration, and the ailments that the plants are used to treat. We found that the Kenyah people use a wide variety of plant species for medicinal purposes and that these plants are used to treat a range of ailments, including diabetes, release urine, pain relief and digestive disorders. The plants are prepared and administered in a number of different ways, including boiling, sun drying and grounding; and also administered either internally or externally. The Bland-Altman plot for agreement analysis revealed that the mean difference between the two sets of measurements i.e demographic description of respondents and method of uses for reported medicinal plants was small and within the limits of agreement. Our results provide important insights into the medicinal plant practices of the Kenyah people and add to our understanding of the traditional medicine practices of indigenous communities in Malaysia. Further research is needed to fully understand the medicinal properties of these plants and the optimal ways in which they should be used to treat various ailments. This research can inform the development of new pharmaceuticals, and contribute to the conservation of important plant species. It is also a valuable resource for understanding the cultural and social context in which these plants are used, and the ways in which they are integrated into the traditional medicine practices of indigenous communities. Keywords: Ethnomedicinal, Traditional medicine, Kenyah, Malaysia